Chinese Organizations in Transition: Changing Promotion Patterns in the Reform Era - Zhao, Wei; Zhou, Xueguang (Organization Science, 2004)
Since the 1980s, the People's Republic of China has embarked on a path of economic transformation that has led to profound changes in organizations. Based on work histories of a sample of urban residents drawn from 14 Chinese cities in six provinces, we assess the extent and direction of organizational transformation by analyzing changes in promotion patterns between the prereform era (1949–1979) and the reform era (1980–1994). We begin with Walder's dual-path model and examine distinctive mechanisms for promotion along two institutionalized—administrative and professional—career lines. We enrich Walder's model by considering the impact of macropolitical processes on career dynamics and the effect of emerging market mechanisms on different organizational sectors. Our findings show that there have been both continuity and significant changes in the criteria and opportunities of promotion in Chinese organizations across the two periods. In the reform era, more educated managers who were recently recruited into the organizations had the highest probability of being promoted. There were also significant variations in promotion patterns across career lines and organizational sectors, reflecting the impacts of both institutional persistence and emerging market forces.